Worship Traditions in Chinese New Year: Origin, Meaning and Changes - Luengsaksri, Napatsorn (Journal for Developing the Social and Community, 2019)
Chinese New Year is the most important festival of the both mainland Chinese and Chinese-Thai people. At present, we are accustomed to seeing many different style of offering ceremony, from the very traditional style to the modern style. The variety of worship food and the step of ceremony become less due to economic problem of each family which is the main factor for this change. This article took the information knowledge of origin, meaning and changes of Chinese New Year’s tradition from mainland Chinese that inherited to Chinese-Thai people in Thailand, which is divided into form of worship in the past and present. This article made for study and shows the factors that affect changes result in the Chinese New Year tradition to the offering and pray to ancestors of the Chinese-Thai people.